The evaluation of long-term screw pull-out rates following posterior thoracolumbar fusion surgery with short and thin pedicle screws - Umit Kocaman; Hakan Yilmaz (Romanian Neurosurgery, 2019)
Background. The aim of this study was to evaluate screw pull-out rates after fusion operations with short and thin pedicle screws. Methods. A total of 200 posterior lumbar and thoracolumbar fusion operations performed at our clinic with short and thin pedicle screws (5.5x35 mm) were retrospectively evaluated. The patients were assessed with computed tomography postoperatively on the day of surgery and at the 6th month. Single groove retraction of the transpedicular screw was evaluated as pull-out. The results were evaluated by the 'number of pull-out cases / total number of cases' and also the 'total number of pull-out screws / total number of screws used' ratios. Results. There were 112 (56%) female and 88 (44%) male patients with a mean age of 58 years. The total number of screws used in the 200 cases was 1188. There were 88 (7.4%) thoracic pedicle screws, 1056 (88.9%) lumbar pedicle screws and 44 (3.7%) sacral pedicle screws used. No pull-out was found in the control CTs taken postoperatively. Left side T11 and T12 pull-out was observed in one case and left L4 pull-out was observed in another case in the control CTs taken at the postoperative 6th month. Pull-out was observed in 2 (1%) of the 200 cases and 3 (0.25%) of the 1188 screws. Conclusions. All the short and thin pedicle screws used had passed the pedicle length and neurocentral junction. The use of a 5.5x35 mm screws in fusion operations is less invasive than using longer and thicker screws while the pull-out rates may be similar.